Performance of mechanical ventilators at the patient's home: a multicentre quality control study. Issue 5 (7th February 2006) - Farré, R; Navajas, D; Prats, E; Marti, S; Guell, R; Montserrat, J M; Tebe, C; Escarrabill, J
Abstract : Background: Quality control procedures vary considerably among the providers of equipment for home mechanical ventilation (HMV). Methods: A multicentre quality control survey of HMV was performed at the home of 300 patients included in the HMV programmes of four hospitals in Barcelona. It consisted of three steps: (1) the prescribed ventilation settings, the actual settings in the ventilator control panel, and the actual performance of the ventilator measured at home were compared; (2) the different ventilator alarms were tested; and (3) the effect of differences between the prescribed settings and the actual performance of the ventilator on non-programmed readmissions of the patient was determined. Results: Considerable differences were found between actual, set, and prescribed values of ventilator variables; these differences were similar in volume and pressure preset ventilators. The percentage of patients with a discrepancy between the prescribed and actual measured main ventilator variable (minute ventilation or inspiratory pressure) of more than 20% and 30% was 13% and 4%, respectively. The number of ventilators with built in alarms for power off, disconnection, or obstruction was 225, 280 and 157, respectively. These alarms did not work in two (0.9%), 52 (18.6%) and eight (5.1%) ventilators, respectively. The number of non-programmed hospital readmissions in the year before the study did not correlate with the index of ventilator error. Conclusions: This study illustrates the current limitations of the quality control of HMV and suggests that improvements should be made to ensure adequate ventilator settings and correct ventilator performance and ventilator alarm operation.